Bactericidal and Cytotoxic Activities of Polyphenol Extracts from Solanum tuberosum spp. tuberosum and spp. andigena Cultivars on Escherichia coli and Human Neuroblastoma SH-SY5Y Cells In Vitro. (22nd March 2018) - Silveyra, María Ximena; Lanteri, María Luciana; Damiano, Rocío Belén; Andreu, Adriana Balbina
Abstract : Potatoes ( Solanum tuberosum L.) are a good source of dietary antioxidant polyphenols. This study investigated the potential antioxidant, bactericidal, and cytotoxic activities in vitro of the phenolic compounds present in tubers of one S. tuberosum spp. tuberosum (Summerside), and three S. tuberosum spp. andigena (landraces Moradita, Waicha, and Santa María) cultivars. Both the content of phenolic acids, chlorogenic acids (CGAs) being the most abundant, and the antioxidant activity were higher in extracts from skin than from flesh. Extracts from Moradita flesh and Summerside skin showed bactericidal activity against Escherichia coli ATCC 25922 but failed to inhibit pathogenic E. coli O157. Both extracts lack pigmentation but do contain 5-CGA, caffeic, and ferulic acids. Positive control with gentamicin and commercial 5-CGA resulted in a complete inhibition of bacterial growth. In addition, all potato extracts and commercial 5-CGA diminished dose-dependently human neuroblastoma SH-SY5Y cell viability. Skin extracts were more potent than flesh extracts. Among flesh extracts, Moradita was the most potent. Together, our results suggest that Moradita flesh could provide a desirable source of important health-promoting substances. Findings indicate that the biological activity of potato extracts is a combination of various bioactive compounds and contribute to the revalorization of potato as a functional food.